(untitled) (Experimental biology, 2019)
The article gives a geobotanical characteristic and floristic analysis of communities with the participation of the narrow-endemic species Rosa iliensis Chrshan. in the floodplains of the Ili river below the Kapchagai hydroelectric station in the low-mountainous area of Malaisary, Almaty region. The authors note that Rosa iliensis Chrshan. is indeed a narrow endemic plant that grows in the floodplains of the Ili River. The plant occupies a limited area and its range is broken due to the construction of the Kapchagai hydroelectric station. A significant part of the floodplain of the Ili River, starting from the Ayakkalgan resort area to the Kapchagai hydroelectric bridge, has been completely flooded. The life status of Rosa iliensis Chrshan. in the floodplains of the Ili River in the region of the low-mountain massif of Malaisary can be considered satisfactory. Since its rare bushes bloom here and bear fruit every year. However, within the population we did not find either the seedlings or the juvenile individuals of this plant. This suggests that the renewal of Rosa iliensis Chrshan. through the seminal path here has almost stopped. Given this, the authors recommend constantly monitoring where the narrow-endemic species of Rosa iliensis Chrshan. is growing and thus keeping the population state under control. Key words: population, coenopopulation, association, dominant, edificator, life form, ecotype.